A Qualitative and quantitative approach about a ludic strategy for teaching-learning: The triominoes of genetics - Clarindo , Wellington; Ferreira da Conceição, Suelen; Weiss, Andreia; de Souza Marçal, Tiago; Ferreira, Adésio (Guará Journal, 2022)
Learning  is  a  systematic  and  interactive  process  that  involves  the  exchange  of  information  between  pupils  and  teachers.  The  knowledge  constructed  during  the  learning  process  represents  the  basis  for  the  cognitive,  emotional  and  psychomotor  edu-cation  of  the  student,  further  contributing  to  the  teacher’s  for-mation.  Among  the  different  subjects  approached  during  basic  education,  and  especially  secondary  school,  Genetics  is  one  that  presents  complex  concepts,  making  it  difficult  for  pupils  to  comprehend and therefore learn. With the aim of facilitating the process  of  teaching-learning  the  basic  concepts  of  Genetics,  the  present study elaborated and applied a new ludic proposal, the game Triominoes. In this scope, Triominoes was created with 40 triangular  tiles  containing,  on  each  face,  complementary  terms  and concepts. Based on the answers to a questionnaire applied after  the  activity,  this  ludic  strategy  was  analyzed  qualitatively  and  quantitatively.  Through  these  analyses,  the  Triominoes  hel-ped  in  the  teaching-learning  process,  the  development  of  logi-cal-deductive  reasoning,  exploring  the  cognitive,  emotional  and  psychomotor abilities of the learners. Therefore, Triominoes can be  considered  an  innovative,  viable  and  low-cost  pedagogical  material, which could be routinely employed for the teaching of Genetics as well as other contents from different subjects of the basic, secondary and higher education.
Keywords: Didactic game; Domino; Genetic teaching; Learning; Ludic